2019
DOI: 10.1021/acs.molpharmaceut.9b00110
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Nitroprusside on Silica Nanoparticles—A Strategy for Safer Use of This NO Donor in Therapy

Abstract: Silica-based nanoparticles have been developed as powerful platforms for drug delivery and might also prevent undesired side effects of drugs. Here, a fast method to synthesize positively charged mesoporous silica nanoparticles (ζ = 20 ± 0.5 mV, surface area = 678 m 2 g −1 , and 2.3 nm of porous size) was reported. This nanomaterial was employed to anchor sodium nitroprusside (SNP), a vasodilator drug with undesired cyanide release. A remarkable incorporation of 323.9 ± 7.55 μmol of SNP per gram of nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Most of these nanoparticles showed that SNP was released by measuring free iron, ,, which can be misleading. Three nanomaterials showed evidence of NO release either by using a direct NO sensor , or indirectly measuring its decomposition product (nitrite) . Interestingly, there is only one nanomaterial that researchers measured cyanide release and even showed it was mainly trapped by the nanoparticle .…”
Section: Nanoparticles In Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these nanoparticles showed that SNP was released by measuring free iron, ,, which can be misleading. Three nanomaterials showed evidence of NO release either by using a direct NO sensor , or indirectly measuring its decomposition product (nitrite) . Interestingly, there is only one nanomaterial that researchers measured cyanide release and even showed it was mainly trapped by the nanoparticle .…”
Section: Nanoparticles In Drug Deliverymentioning
confidence: 99%
“…Drug delivery and potential nitroprusside carriers: (i) TEM images of nanoparticles of MNP-SNP illustrate their sizes and porosity enabling expressive drug binding; (ii) it illustrates a proposal of how cyanide release was reduced by nanocarrier’s nature (e.g., cyanide adsorption on the positively charged surface of the carrier); (iii) therapeutic effects versus conventional (black ---) and controlled-release drug administration (red ---); and (iv) possible curtail of leaching losses on topical administration of this nanomaterial.…”
Section: Nanoparticles In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the ligand 2 and 5 and the complex 6 were also tested for comparison. The NO species is indeed known to induce vasodilation of blood vessels, and NO carrier molecules, such as sodium nitroprusside (SNP, Na 2 [Fe II (CN) 5 (NO)), have an important therapeutic effect for hypertensive crises [40]. At the same time, HNO, the reduced and protonated form of NO .…”
Section: Vasodilatory and Antihypertensive Activitymentioning
confidence: 99%
“…Nitric oxide (NO) is an important messenger molecule which has a wide range of physiological functions. In vivo, nitroglycerin, sodium nitroprusside (SNP) and other NO donors release high amount of NO capable of inducing apoptosis in tumor cells (14,15). In a previous study, the secretion of IFN-γ by spleen cells in mice treated with andrographolide was significantly increased relative to the control, suggesting that andrographolide increases the specificity of cellular immunity (9,16).…”
Section: Introductionmentioning
confidence: 99%